MicroRNA-126: Dual Role in Angiogenesis Dependent Diseases - Nammian, Pegah; Razban, Vahid; Tabei, Seyed M. B.; Asadi-Yousefabad, Seyedeh-Leili (Current Pharmaceutical Design, 2020)
Background: MicroRNA-126, a microRNA implicated in blood vessel integrity and angiogenesis is significantly up/down regulated in different physiological and pathological conditions related to angiogenesis such as cardiovascular formation and angiogenesis dependent diseases. MicroRNA-126 plays a critical role in angiogenesis via regulating the proliferation, differentiation, migration, and apoptosis of angiogenesis related cells such as endothelial cells. Objective: The aim of this review is to investigate the molecular mechanisms and the effects of microRNA-126 on the process of angiogenesis in pathophysiological conditions. Methods: To conduct this review, related articles published between 2001 and 2019 were collected from the PubMed, Web of Science, Google Scholar, Scopus and Scientific Information Database using search terms such as microRNA-126, angiogenesis, cardiovascular disorders, hypoxia, VEFG-A, endothelial cells, VEGF pathway, and gene silencing. Then, the qualified articles were reviewed. Results: MicroRNA-126 regulates the response of endothelial cells to VEGF, through directly repressing multiple targets, including Sprouty-related EVH1 domain-containing protein 1 (SPRED1) and phosphoinositol-3 kinase regulatory subunit 2 (PIK3R2/p85-b). MicroRNA-126 -3p and microRNA-126 -5p have cell-type and strandspecific functions and also various targets in angiogenesis that lead to the regulation of angiogenesis via different pathways and consequently diverse responses. Conclusion: MicroRNA-126 can bind to multiple targets and potentially be both positive and negative regulators of gene expression. Thus, microRNA-126 could cause the opposite biological effects depending on the context. As a result, understanding the different cellular pathways through which microRNA-126 regulates angiogenesis in various situations is a critical aspect in the development of novel and effective treatments for diseases with insufficient angiogenesis.
Keywords: microRNA-126